The influence of reflective thinking on prospective teachers’ skills and frequencies of their use of constructivist learning principles [Yansıtıcı Düşünmenin Öğretmen Adaylarının Yapılandırmacı Öğrenme Ortamı Hazırlama Becerileri ve Becerileri Kullanma Sıklıklarına Etkisi] - (:unkn) unknown (Ankara University, 2015)
The purpose of this study was to determine the influence of reflective thinking practices on prospective teachers’ skills in preparation of the constructivist learning environment and frequencies of the their use of constructivist learning environment principles at the Teaching Practice Course II. Sixteen prospective teachers (eight female, eight male), taking the Teaching Practice II course in the Department of Elementary Education at Marmara University, participated in this study. The Embedded design, a mixed methods design, was used. At the beginning of the study, there was no significant difference between constructivist learning environment preparation skills of the prospective teachers in both experimental and control groups. At the end of the reflective thinking practices, there was a significant difference between experimental and control groups’ protest scores in relation to constructivist learning environment preparation skills’ favoring the prospective teachers in the experimental group. Analysis of the observations made during the implementation and it was observed that prospective teachers in the experimental group used the constructivist learning environment skills during teaching practice more often. © 2015, Ankara University. All rights reserved.
Keywords: Constructivist learning; Prospective elementary teachers; Reflective thinking; Teaching practice